Perlindungan Hukum terhadap Pengelola Terminal Peti Kemast Terhadap Kerusakan Peti Kemas dalam Pelayanan Bongkar Muat Peti Kemas - Z. Intan B. Bulan; Hulman Panjaitan; Wiwik Sri Widiarty (Syntax Idea)
This academic article aims to analyze the legal protection for container terminal operators regarding container damage that occurs during the loading and unloading processes at container terminals. Container terminals are crucial components in the logistics and international trade supply chain, and container damage during the loading and unloading processes can lead to serious consequences, including financial losses and shipment delays. This research documents the legal framework governing the obligations and responsibilities of container terminal operators in the loading and unloading services. The article discusses the legal aspects that regulate the responsibilities of terminal operators related to container management, procedures for damage claims, and compensation mechanisms for container owners. Additionally, the study analyzes common issues that arise in container loading and unloading practices, including regulatory ambiguities, differences in contract interpretation, and challenges in proving damage occurring during transportation. In this analysis, the impact of legal regulations on the responsibilities of container terminal operators and the role of dispute resolution institutions in handling damage claims will be considered. The research also evaluates ways to enhance legal protection for container terminal operators and container owners. The research findings highlight the need for improvements in the implementation and understanding of legal aspects related to legal protection for container terminal operators against container damage in loading and unloading services. This article contributes to a deeper understanding of the legal framework governing responsibilities in the container terminal industry and promotes improvements in regulations and industry practices that are fair and transparent.